La riapertura e la valorizzazione dei navigli come progetto di paesaggio e nuovo modello di vivibilità urbana per Milano - Boatti, Antonello (Ri-Vista. Research for landscape architecture, 2017)
The reopening of the canals in Milan is an ambitious challenge for a city that wants to change the sign of liveability and sustainability, and in particular for Milan which has based its story and its development over the centuries on being a city of water. The research explores everything that can be involved with the reopening of the canal system in Milan from the North -East of the city, where the Martesana is still open, toward the centre of the city where the canal finds the historic circular path on his eastern side, until reaching the recently reopened dock for ships known as the "Darsena" to finally rejoin the canals "Pavese" and "Grande", today still in function. An environmental project, able to ensure navigability for small boats, for a new landscape and for recovering identity, all looking to the future, but also full of poetry as narrated by the beautiful images of the Multiverso association.